Yttrium-90 selective internal radiotherapy as bridge to curative hepatectomy for recurrent malignant solid pseudopapillary neoplasm of pancreas: case report and review of literature. Issue 9 (25th September 2020) - Dyas, Adam R; Johnson, David Thor; Rubin, Erin; Schulick, Richard D; Kumar Sharma, Piyush
Abstract: Recurrent malignant solid pseudopapillary neoplasms of the pancreas (SPNP) are rare tumors with unpredictable clinical and histopathological features. There is a lack of consensus regarding utilization of adjuvant modalities in conjunction with or in lieu of curative metastatectomy. We present a remarkable case where Yttrium-90 selective internal radiation therapy (Y-90 SIRT) was successfully utilized to elucidate underlying tumor biology and aid resection of a large multifocal recurrent metastatic SPNP in the right hemi-liver of a 59-year-old female. Thus, in cases where curative metastatectomy remains the treatment goal in management of recurrent and/or metastatic SPNPs, Y-90 SIRT is a safe and effective adjunct treatment to facilitate curative resection.